Evaluation of the effectiveness of a multimodal aspiration prevention system in stroke rehabilitation nursing - Xibo Sun; Xiulan Wu; Yamei Zhang; Ming Lu; Chongrui Feng; ChuRong Liu; YouMing Gu; FaHua Lu; LiRong Liu; Gengbiao Zhang; Zulin Dou; Zhanhao Liu (PLoS ONE, 2026)
Objective To evaluate the efficacy of the Multimodal Aspiration Prevention System (MAPS) in reducing aspiration incidence, preventing pneumonia, and improving swallowing function in stroke rehabilitation patients. Methods A before-after controlled study was conducted involving 855 stroke rehabilitation patients (408 in the MAPS intervention group, 447 in the historical control group). The intervention group received MAPS, including a three-tier risk warning system, standardized intervention procedures, and multidisciplinary collaboration, while the control group received conventional care. Primary outcomes included overt aspiration incidence, with secondary outcomes assessing stroke-associated pneumonia rates, swallowing function improvement, psychological status, and patient satisfaction. Results The MAPS group demonstrated a significantly lower incidence of overt aspiration compared to control group (p < 0.05), with complete elimination of aspiration events achieved by the second month of implementation. Secondary outcomes revealed clinically meaningful improvements following MAPS adoption: stroke-associated pneumonia rates decreased substantially (p < 0.05), psychological assessments indicated significant alleviation of anxiety and depression symptoms (p < 0.05), and patient satisfaction scores reached 99.2%. Although swallowing function showed numerical improvement in the MAPS group, the difference did not reach statistical significance when compared to the control group (p > 0.05). Conclusion MAPS effectively reduces aspiration and pneumonia risks while enhancing psychological well-being and patient satisfaction in stroke rehabilitation. Its closed-loop management model demonstrates clinical applicability. Further multicenter studies are warranted to validate long-term benefits.